Prior iontophoresis of saline enhances vasoconstriction to phenylephrine and clonidine in the skin of the human forearm - Drummond, Peter D. (British journal of clinical pharmacology, 2002)
Aims  To determine whether postjunctional α1‐ and α2‐adrenoceptors mediate vasoconstrictor responses in the cutaneous vasculature of the human forearm. Methods  Drugs were administered transdermally by iontophoresis in the forearm of 20 healthy participants. Phenylephrine and clonidine were administered at sites pretreated with the relevant antagonist (terazosin and rauwolscine), and at additional untreated sites and sites pretreated with saline. To enhance the contrast between sites, the forearm was heated to 42° C before flow was measured with the laser Doppler technique. Results  After the iontophoresis of phenylephrine, blood flow at the site pretreated with terazosin was 24±37% (±95% confidence interval) greater than flow at the reference site, whereas flow was 53±24% lower than reference flow at the previously untreated site and 77±10% lower than reference flow at the site pretreated with saline (P<0.001). After the iontophoresis of clonidine, blood flow at the site pretreated with rauwolscine was 25±21% greater than flow at the reference site, whereas flow was 56±15% lower than reference flow at the previously untreated site and 72±8% lower than reference flow at the site pretreated with saline (P<0.001). The saline pretreatment enhanced vasoconstriction to phenylephrine (P<0.05) and clonidine (P=0.05). Conclusions  Pre‐treatment with the appropriate antagonist blocked vasoconstrictor responses to phenylephrine and clonidine, consistent with the presence of both α‐adrenoceptor subtypes in cutaneous vessels of the human forearm. In addition, iontophoretic pretreatment with saline facilitated vasoconstrictor responses, suggesting that a nonspecific effect of iontophoresis may enhance drug penetration through the stratum corneum.